Australian industrial relations in 2018: Inequality, policy stagnation and a brewing storm. (June 2019) - Clibborn, Stephen
This article introduces the Journal of Industrial Relations ' Annual Review of Industrial Relations in 2018. Providing an overview of the other articles contained in the Annual Review issue, this article discusses industrial relations policy stagnation, and manoeuvring for change from both employer and employee representatives. With leadership uncertainty and change within the federal government, it has been a quiet year for industrial relations reform, although some key decisions from courts and tribunals are examined and some states' return to private sector regulation noted. A number of questions are raised regarding potential for reform in 2019 and for how to conceptualise industrial relations change.